Nostalgia como explicadora do bem-estar subjetivo: o papel mediador dos valores humanos - Ribeiro, Maria Gabriela Costa (2020)
This dissertation aimed to verify to what extent the nostalgia and human vales explain the subjective well-being. Four studies were conducted. The Study 1 aimed to develop the Dispositional Nostalgia Scale (DNS) and investigate its psychometric indexes (e.g., factorial and convergent validities, reliability). Participants (N = 207 undergraduate students; Mage = 22.8; SD = 6.13; 51.0% men) completed the initial version of the DNS, composed by 20 items, the Nostalgia Inventory (NI), the Southampton Nostalgia Scale (SNE) and demographic questions. An exploratory factor analysis (principal axis factoring; oblimin rotation) indicated a one-factor solution and satisfactory reliability (α = 0.86). However, it was decided to select the items with factor loading above |0.50| under the same previous criterions. The final version, composed by 10 items, showed again a one-factor solution (α = 0.84) and convergent validity was supported (NI, r = 0.57; ENS, r = 0.31). The Study 2 aimed to confirm the previous factor solution for the DNS found in the first study. Participants (N = 260 undergraduate students; Mage = 22.3; SD = 5.92; 53% women) completed the DNS brief version, the NI, the SNE and demographic questions. The confirmatory factor analysis revealed that the error term of item 8 was correlated with the items 2 and 10. The confirmatory model was reestimated, in absence of the item 8, and the one-factor solution fitted well (e.g., CFI = 0.94; TLI = 0.91; RMSEA = 0.06) with satisfactory reliability (α = 0.78; test-retest, t1 and t2= 0.82). Moreover, the DNS brief version was correlated with NI (r = 0.55) e SNE (r = 0.36). In the Study 3 was investigated the relations between nostalgia, human values and variables that composes the subjective well-being universe (meaning of life, self-esteem and optimism). Participants (N = 306 undergraduate students; Mage = 24.9; SD = 7.86; 62% women) completed the DNS, Basic Values Survey, Meaning in Life Questionnaire, Rosenberg Self-Esteem Scale, Positive and Negative Affects Scale and demographic questions. The DNS correlated positively with interactive values (r = 0.18), excitement (r = 0.13) e suprapersonal (r = 0.14) and negative affects (r = 0.13). In turn, the DNS correlated negatively with presence of sense (r = -0.14). It was not observed correlations with self-esteem and positive affects. Moreover, the predictive power of nostalgia was tested on self-esteem and presence of sense, including the interactive values as a mediator variable; a positive indirect effect was observed. In addition, the interactive values showed a suppressor effect on the estimated mediation model. Finally, the Study 4 aimed to verify the state nostalgia effect on optimism mediated by interactive values and self-esteem and whether this effect is contingent of on trait nostalgia. Participants (N = 193 undergraduate students; Mage = 24.3; SD = 7.61; 65% women) completed the same instruments of the Study 3 and the Optimism Scale. In sum, the effect of the state nostalgia and the interaction term (state nostalgia x trait nostalgia) on optimism through sequential path (interactive subfunction and self-esteem) was not significant. However, the trait nostalgia explained the optimism when mediated by interactive values and self-esteem. In conclusion, it was verified the development of a reliable instrument to measure the trait nostalgia. In addition, the importance of a social function on the nostalgia construct was supported, once individuals with higher nostalgic experiences endorse Affectivity, Belonging and Support values and, in turn, exhibits higher levels of subjective well-being (meaning of life, self-esteem and optimism).